ORGANOLEPTIC PROPERTIES OF LOHAN FISH MEATS - Geovany Idilha Putri; Sanya Anda Lusiana; Budi Kristanto; Nia Budhi Astuti (POLTEKKES KEMENKES JAYAPURA, 2022)
Due to the high prevalence of undernourished children, it is necessary to improve their nutritional status through food-based nutrition intervention. Lohan fish is one of the high protein food. The study aimed to analyze the organoleptic properties of lohan fishball. The research type was quasi-experimental with a one-shot case study design on lohan fishballs' organoleptic properties (color, taste, aroma, and texture). The treatment formulation compared three proportions of lohan fish and tapioca flour, namely, F1 50: 50, F2 60: 40, and F3 70: 30. Data analysis was performed using a descriptive method. The hedonic test results showed the most preferred formula was F2 for each attribute: color 55%, aroma 40%, 60% texture, and taste 45%. Keywords: Fishball, Lohan fish, Organoleptic test